Evaluating the Financial Performance of Indonesian Fintech Lending Firms During and Post COVID-19 - Surwanti, Arni; Rahmawati, Indah (Journal of Economics and Management Scienties, 2025)
The COVID-19 pandemic has disrupted the world economy. Technological developments in the financial sector make it easier for everyone to carry out activities and transactions. Fintech lending is one of the fintech in great demand since the COVID-19 pandemic, where people can apply for credit other than through banking. Fintech lending distribution has increased since the pandemic and has affected the financial performance of fintech lending companies. This research aims to analyze whether there are changes and differences in the financial performance of fintech lending companies during and after the pandemic. The research object is a fintech lending company registered with Indonesia's Financial Services Authority (OJK). This research uses a data analysis tool in the form of SPSS version 26. The results of this research show that the performance of fintech lending companies shows that there have been changed in terms of liquidity, solvency, activity, and profitability during and after the pandemic. The analysis results on the current ratio, fixed asset turnover ratio, total debt to total assets ratio, and bad debt ratio show differences in performance during and after the COVID-19 pandemic. Meanwhile, the cash ratio, receivables turnover ratio, average receivables turnover period, ROA, and ROE show no difference in the financial performance of fintech lending companies during and after the COVID-19 pandemic.